'"Loving hearts" and "brave ones": slavery, family, and the problem of freedom in antebellum America'. (2nd July 2020) - de Schweinitz, Rebecca
ABSTRACT: This essay argues that formerly enslaved people participated in antebellum conversations about slavery and freedom, defining both in terms of the liberty and integrity of families. While liberal republican ideology insisted that an unquenchable love of liberty would lead worthy men to rise up and claim their freedom, ex-slave narratives insisted that deserving black men and women might sacrifice personal liberty in the name of family values. Nineteenth-century political theory commonly associated freedom with 'autonomous, self-directed individuals.' Black Americans, however, suggested a collective, contingent version of liberal republicanism which reflected their own ethics, brought together the intellectual and emotional foundations of anti-slavery thought, and made abolitionism especially meaningful to a growing middle class that increasingly valorized sentimental conceptions of family.